Short Time Synthesis of Titania Nanotubes: Effect of Pre-Mixing Prior Hydrothermal - Indriana Kartini; Ira Nur Arba’atul Jannah; Fitri Rizki Amalia; Salim Mustofa; Eko Sri Kunarti; Respati Tri Swasono (Universitas Gadjah Mada, 2019)
The effect of pre-mixing by mechanical stirring before hydrothermal and hydrothermal time on the crystalline phases and morphology of titania has been studied. It was shown that nanotubes titania can be obtained after 5 h hydrothermal at 150 °C. The XRD patterns and Raman spectra of the produced powders showed the existence of anatase and titanate crystalline phases. At the longest stirring, TiO2 (B) was observed. High textural coefficient for [200] plane of anatase (TC200) confirmed oriented growth of one-dimensional anatase along [200]. All powders resulted at various stirring time were nanotubes, as confirmed by Transmission Electron Microscope (TEM). It was found that the longer the stirring, the higher the surface area of the nanotubes. All powders showed type-IV isotherm for nitrogen gas adsorption/desorption, indicating the existence of mesoporous materials. However, long hydrothermal induced the nanospheres formation, hence reducing the surface area. The band-gap of the resulted titania nanotubes were ranging from 3.11–3.16 eV. The photocatalytic performance toward the degradation of methylene blue of the titania nanotubes was higher ( 50%) compared to the bulk TiO2 ( 5%) under visible-light and was comparable under UV-light ( 60%). These results pave a way of producing visible-sensitive TiO2 photocatalyst by altering the morphology.